PROGRAM GOVERNMENT PUBLIC RELATIONS UNTUK MENINGKATKAN PARTISIPASI MASYARAKAT KOTA SEMARANG DALAM MENGGUNAKAN LAPOR SEMAR SOLUSI AWP SEBAGAI KANAL PENGADUAN RESMI KOTA SEMARANG SEBAGAI STRATEGIC MANAGER & CONTENT PLANNER - Jasmine Ramadhania Puteri; Lintang Ratri Rahmiadji (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2026)
Although Lapor Semar Solusi AWP has been launched as a public complaint channel, the number of users of this service is still not proportional to the population of Semarang City. Initial survey results indicate that some people are not fully aware of the service's existence, while others still doubt the follow-up of submitted reports. This condition indicates a gap between the public's need to express aspirations and the level of use of official complaint channels. This field of work aims to implement a Government Public Relations strategy to increase awareness, trust, and public participation in the use of Lapor Semar Solusi AWP. The communication program is implemented through the Cipta Seni Bahana Aspirasi #NgadudiLaporSemar campaign implemented through Goes to School, Goes to Campus, Goes to RW (Community Unit) activities, as well as main events that combine educational approaches and public interaction. The campaign is also strengthened through the use of digital media and media publications to expand the reach of information. The implementation results show that the implemented communication strategy is able to increase public awareness, strengthen trust in the service, and encourage an increase in the number of users